Subnational Data Requirements for Fiscal Decentralization : Case Studies from Central Eastern Europe - Yilmaz, Serdar; Hegedus, Jozsef; Bell, Michael E. (Washington, DC: World Bank, 2013)
Poverty is an outcome of interaction between economic, social, and political forces. The World Bank has emphasized poverty reduction in its programs and operational activities. With the launching of initiatives such as the poverty reduction strategy papers and the Comprehensive Development Framework, it has made considerable progress in integrating antipoverty programs into other lending operations. As mentioned in the World Development Report 2000/2001, Attacking Poverty (World Bank 2001b), poverty has many dimensions. It is not defined only by income, but also has political and sectoral (access to services) dimensions. Today, in most countries subnational governments are responsible for the delivery of services that affect these dimensions of poverty. Because subnational governments control increasingly higher shares of total public resources, their competence in designing public policies and delivering public services becomes crucial in influencing the level of poverty. Indeed, the literature on fiscal decentralization presents evidence that local services, especially health and education, are highly correlated with the incidence of poverty (Bird and Rodriguez 1999). In this context, the need for subnational demographic, social, economic, and fiscal data is becoming more evident at a time when subnational governments are involved in national and global objectives of poverty reduction. Statistical capacity building at the subnational level aims to help statistical offices and subnational governments produce the basic microdata necessary not only for monitoring progress in poverty reduction, but also for ex ante policy formulation by subnational governments.